Isu Geopolitik Timur Tengah dalam Kolaborasi Musik 'Ilahu ats Tsaurah' - Shinta Fitria Utami (Jurusan Bahasa dan Sastra Arab Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2020)
This research is an interdisciplinary study involving the fields of literature and political science on musical collaboration entitled Il?hu ats-Tsaurah. This paper uncovers the relationship between the musical collaboration and geopolitical issues and the worldviews of the musicians involved in the conflict. This research will use the theory of Genetic Structuralism to dissect the contents of the lyrics in the Il?hu ats-Tsaurah music collaboration. The results of the study show that the geopolitical issue of the Middle East is one of the factors causing the prolonged conflict and the world view of the musicians shows their disappointment as an Arab nation which is now increasingly divided due to differences in race, religion, and country. Through this musical collaboration, the musicians also urge the Arabs to unite and not just be silent when they find out that their brothers are being oppressed.